P3.111 Optimising STI screening in hiv-infected men who have sex with men (MSM). (8th July 2017) - Dionne-Odom, Jodie; Aaron, Kristal; Daniels, Brice; Hook, Edward W; Pol, Barbara Van Der
Abstract : Introduction: Current CDC guidelines recommend screening "at least annually" for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) at sites of exposure using nucleic acid amplification tests (NAAT) in HIV-infected MSM. National screening rates remain suboptimal in this high-risk population, particularly at extra-genital sites. Methods: We enrolled HIV-infected MSM from a routine care visit at the 1917 HIV clinic in Birmingham, Alabama. Inclusion criteria included age >18, receptive anal intercourse in the past 30 days and lack of antibiotic exposure. Participants provided four self-collected rectal swabs and a urine sample. A pharyngeal sample was provider-collected. Samples from the rectal and genital sites were run on four testing platforms with the composite infection standard (≥2 NAAT positive) defining a positive result. Pharyngeal samples were run on two platforms and the patient infection standard (2 NAAT positive) was used to define positivity. Results: A total of 175 unique HIV-infected MSM were enrolled between December 2014 and November 2016. Overall, 34 men (19.4%) had CT or GC infection detected. CT infection rates by site were: 13.1% rectal, 3.4% urogenital, 0% pharyngeal. GC infection rates by site were: 8.6% rectal, 3.4% urogenital and 2.3% pharyngeal. In addition, 5.7% of men had co-infection with CT and GC at the rectal site and 1.7% had simultaneous CT or GC infection at genital and rectal sites. Most infections (79.4%) would have been missed by genital screening alone. Conclusion: Sexually active, HIV-infected MSM in Birmingham, Alabama have high prevalence rates of CT and GC infection, particularly at the rectal site. This has public health implications since CT/GC coinfection may increase HIV transmission rates. Clinics that provide care for HIV-infected MSM should streamline extragenital testing; this may include the incorporation of patient-collected rectal swabs into routine care.